EFL Teachers' Job Burnout Its Associated Factors: Public Primary School of Jimma Zone in Focus (GIST – Education and Learning Research Journal, 2024)
Because of environmental and personal factors, EFL teachers are often exposed to job burnout. However, the problem and factors that form causal associations seem ignored in the context of the study. This study, thus, aims to investigate EFL teachers' burnout and its associated factors among public primary schools in Jimma Zone, Ethiopia. A mixed methods research design was used for the study. Cluster sampling and judgmental sampling techniques were employed to select 100 EFL teachers, and a questionnaire and an interview were utilized to collect data. Both descriptive and inferential statistics were used for data analysis. The finding shows that the majority of EFL teachers underwent a high level of burnout, and all the hypothesized factors had a significant association with burnout and its dimensions. The major finding is that job burnout negatively affected EFL teachers' work engagement. Considering this finding, the provision of training on coping strategies is recommended. The pedagogical implication of the finding is to incorporate content on emotional intelligence and stress-coping mechanisms in EFL teaching methodology courses. Finally, further study is recommended to be undertaken on a large scale to understand the magnitude of expansion of the problem in the region and nationwide as the sample is small to generalize to these contexts.